Effects of platelets activated by different agonists on fibrin formation and thrombin generation. (1st January 2023) - Muravlev, Ivan A.; Dobrovolsky, Anatoly B.; Antonova, Olga A.; Khaspekova, Svetlana G.; Mazurov, Alexey V.
Abstract: Activated platelets possess procoagulant activity expressing on their surface phosphatidylserine (PS), a substrate for assembling coagulation complexes. We examined the effects of platelets activated by different agonists on fibrin formation and thrombin generation and compared these effects with each other and with PS expression. Modified plasma recalcification assay was developed to assess platelet effects on fibrin formation. Washed human platelets were left intact or activated by A23187 ionophore, collagen, arachidonic acid, ADP or TRAP (Thrombin Receptor Activating Peptide) and spun down in 96-well plates. Plasma was then added, recalcified, and fibrin formation was monitored by light absorbance. Platelets prepared in the same way were tested for their effect on thrombin generation. PS expression was evaluated by flow cytometry using annexin V staining. Platelets significantly accelerated fibrin formation and thrombin generation. They shortened lag phase and increased maximum rate of plasma clotting, and increased peak and maximum rate of thrombin generation. In both tests platelets were presumably activated by endogenous thrombin formed in plasma after triggering coagulation reactions. However, pretreatment with exogenous agonists additionally increased platelet procoagulant activity. It reached the maximum after incubation with A23187, being lower with collagen and arachidonic acid and minimum with ADP and TRAP (the latter might be ineffective due to competition with endogenous thrombin). The effects of platelets activated by different agonists on fibrin formation and thrombin generation correlate with each other and correspond to PS expression on their surface. Plain Language Summary: Why was the study done? Platelets and blood coagulation system interact with each other in hemostasis and intravascular thrombosis. Direct platelet effects on fibrin formation (plasma clotting), the final stage of blood coagulation cascade, have been insufficiently studied. The work is aimed at developing a method for studying platelet participation in fibrin formation in blood plasma and investigating the influence of platelet agonists on this reaction. What is new? Platelets significantly accelerate fibrin formation and their activation with various agonists (thrombin, collagen, arachidonic acid) enhances these effects. Effects of platelets on fibrin formation correlated with their ability to stimulate thrombin generation in blood plasma Effects of platelets on fibrin formation and thrombin generation correlated with the level of phosphatidylserine exposure on their surface What is the impact? This study provides further evidence that platelet procоagulant effects on fibrin formation should be considered in investigations of platelet involvement in hemostatic and thrombotic reactions and in the evaluation of the efficacy of antiplatelet drugs